Analysis Flypapper Effect Influence Local Original Income , General Allocation Fund , Allocation Fund Special Funds and Revenue Sharing Funds for Regional Government Expenditures (Case Study in South Halmahera, Central Halmahera, and East Halmahera Distri - Sunan, Muammil; Husen, Amran; Yetty, Yetty; Maimunah (Journal of Social Science, 2024)
Research purposes This is : (1) Analyze influence income original (PAD) on capital expenditure in South Halmahera Regency , Central Halmahera Regency , and East Halmahera Regency ; (2) Analyzing influence of allocation funds general (DAU) for capital expenditure in South Halmahera Regency , Central Halmahera Regency , and East Halmahera Regency ; (3) Analyzing influence of allocation funds special (DAK) for capital expenditure in South Halmahera Regency , Central Halmahera Regency , and East Halmahera Regency ; (4) Analyzing The influence of profit sharing funds (DBH) on capital expenditure in South Halmahera Regency , Central Halmahera Regency , and East Halmahera Regency ; (5) Analyzing the occurrence phenomenon flypaper effect in South Halmahera Regency , Central Halmahera Regency , and East Halmahera Regency . This study is study studies cases in producing areas mining in North Maluku Province . The analytical tools used in the study is analysis panel data regression . Research results show that income original areas and allocation funds special influential positive towards government spending . While the allocation fund general and profit sharing funds are not influential on government spending area . Research results show that existence phenomenon flypaper effect in Central Halmahera Regency , South Halmahera Regency , and East Halmahera Regency .